1994
DOI: 10.1364/ol.19.001240
|View full text |Cite
|
Sign up to set email alerts
|

Red sensitivity of dichromated cellulose triacetate as a holographic recording material

Abstract: The red sensitivity of dichromated cellulose triacetate holographic recording material without any dye sensitization is reported. We suggest that the sensitivity is due to the absorption at 590 nm of the intermediate Cr(V) formed in the reducing process of chromium from Cr(VI) to Cr(III). In the experiment, the real-time transmission gratings are recorded with 632.8-nm irradiation from a He-Ne laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In 1990s, Guo and co-workers used CA as a holographic material. 12,13 Holograms recorded in this material are very stable and can survive very high humidity. 14 Later it was reported that the material had the property of positive relief modulation which could lead to relief type of micro optical devices.…”
Section: Introductionmentioning
confidence: 86%
“…In 1990s, Guo and co-workers used CA as a holographic material. 12,13 Holograms recorded in this material are very stable and can survive very high humidity. 14 Later it was reported that the material had the property of positive relief modulation which could lead to relief type of micro optical devices.…”
Section: Introductionmentioning
confidence: 86%